2014
DOI: 10.12720/joams.2.1.17-22
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Fraudulent Financial Reporting through Financial Statement Analysis

Abstract: Fraudulent financial reporting is a major concern for two primary regulators of Malaysia's capital market -the Securities Commission (SC) and Bursa Malaysia. Both authorities continue to refine the parameters that will ensure rigorous surveillance over public listed firms. The objective of current study is to examine the association between financial statement analysis and fraudulent financial reporting. Many researchers found indication of financial ratios to detect fraudulent financial reporting but others a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
1
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 16 publications
(25 reference statements)
4
51
1
10
Order By: Relevance
“…Meningkatnya kecurangan mengindikasikan terdapatnya kebutuhan yang tinggi dalam penelitian untuk menemukan metode yang efektif dalam mendeteksi potensi kecurangan pada perusahaan (Dalnial et al, 2014). Salah satu cara yang digunakan untuk mendeteksi kecurangan pada laporan keuangan adalah dengan menggunakan rasio keuangan.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Meningkatnya kecurangan mengindikasikan terdapatnya kebutuhan yang tinggi dalam penelitian untuk menemukan metode yang efektif dalam mendeteksi potensi kecurangan pada perusahaan (Dalnial et al, 2014). Salah satu cara yang digunakan untuk mendeteksi kecurangan pada laporan keuangan adalah dengan menggunakan rasio keuangan.…”
Section: Pendahuluanunclassified
“…Dalnial et al, (2014) menemukan bahwa asset composition 2 dan asset composition 3 memiliki pengaruh terhadap fraudulent financial reporting.…”
Section: Pengaruh Asset Composition Terhadap Fraudulent Financial Repunclassified
See 1 more Smart Citation
“…Several researchers suggest that financial ratios are effective in fraud detection (Bai et al 2008;Subramanyam & Wild 2009;Dalnial et al 2014). In contrast, Kaminski et al (2004) concluded differently in which they argued on the limitations of financial ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Manipulation through the distortion of earnings is a pattern that becomes their focus (Ahmed and Naima, 2016;Anh and Linh, 2016;Dalnial at al., 2014;Kaur at al., 2014;Mahama, 2015;Omar at al., 2014;Paolone and Magazzino, 2014). Their findings appear to be more useful as a medium of knowledge.…”
Section: Introductionmentioning
confidence: 99%